Chemical Composition and Antioxidant Properties of Instant Coffee and Coffee Capsules: Comparative Analysis - Pugacheva A.; Makarova N.; Ignatova D. (Техника и технология пищевых производств, 2019)
Coffee is one of the most popular drinks in the world due to its unique sensory properties, i.e. aroma and taste. Coffee consumption increases from year to year, which makes its functional property a relevant issue. The present research featured the antioxidant component in freeze-dried coffee and coffee capsules obtained from a commercial network. The main objective was to identify the most advantageous types of coffee to serve as a raw material for extract production. Coffee is known to prevent diseases caused by the oxidative action of free radicals. The paper presents a review of multiple scientific sources on the beneficial properties of coffee. It also features some results of the study in the chemical composition of coffee, i.e. dry matter content, phenols, flavonoids, etc. The anti-radical activity was described with the help of the DPPH method, while the FRAP method was employed to study the antioxidant properties of several coffee samples. The samples of instant coffee and coffee capsules were obtained from a distribution network (Samara, Russia) and included such brands as Coffea Premium, Coffesso, Nescafe Dolche Gusto, Jacobs Milicano, Bushido, Egoiste, and Fresco. Coffea Premium and Coffesso showed the best results in all the tests and can be additional sources of antioxidant substances. These two varieties of coffee capsules are produced for capsule coffee machines and are roasted ground coffee beans. Coffea Premium demonstrated the best results in phenolic substances, flavonoids, and anti-radical activity with 1338 mg of gallic acid and 854 mg of catechin per 100g of the original substance and 0.84 mg per cm3. Nescafe Dolche Gusto coffee capsules and such varieties of instant coffee as Jacobs Millicano, and Fresco showed similar but average results according to all the phenolic analyzes. Bushido and Egoiste were found lacking in phenols, flavonoids, and dry substances. These samples demonstrated low values of antiradiation and regenerating ability, which indicates a worse quality than that of coffee capsules. This may be due to some processing peculiarities: instant coffee undergoes thermal treatment when coffee granules are formed, while solvents are used to obtain coffee extract. Thus, the research revealed that Coffea Premium and Coffesso are the best sources of antioxidants.